EXTRACTION OF OIL AND FORMULATION OF PERFUME FROM LEMONGRASS - MOHAMMED, MUSTAPHA BALA; YAMUSA, ABDULLAHI ZAHARADDEEN; MAMMAN, IBRAHIM SANI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Lemon grass (Cymbopogon citratus) essential oil is used in many aspects, such as flavouring industries, medicinal material and food technology. Perfume is a fragrant liquid made from an extract that has been distilled in alcohol and water. The research aimed at perfume production. Extraction of oil from the plant material; formulation of perfume from the extract and the infrared spectroscopy of the essential oil were conducted. Lemon grass leaves, n-Hexane and ethanol are the major materials and reagents used in the extraction process.Essential oil sample was deposited on HATR plates with ZnSe and the FTIR recorded in the range of 4000 – 650 cm-1 by accumulating 64 scans per spectrum with a resolution of 4cm-1. 1.9g (1.3%) and 1.01g (0.67%) of the essential oil were extracted from 150g each of the plant material using solvent extraction and steam distillation methods respectively. The result showed that, solvent extraction method gave a high yield of the oil extracted. FT-IR of the extracted oil sample showed the presence of – OH (33399.7cm-1), ˃C=O (1651.2cm-1), -CH3 (1453.7cm-1), -CH (2929.7cm-1), and ˃C=C˂ (1420.1cm-1). More researches should be carried out on extraction of essential oil using various plant materials due its simple operation method.